Synthesis of Oligonucleotide Conjugates and Phosphorylated Nucleotide Analogues: An Improvement to a Solid Phase Synthetic Approach - Valeria Romanucci; Armando Zarrelli; Lorenzo De Napoli; Cinzia Di Marino; Giovanni Di Fabio (Journal of Chemistry)
An improvement to our solid phase strategy to generate pharmacologically interesting molecule libraries is proposed here. The synthesis of new o-chlorophenol-functionalised solid supports with very high loading (0.18–0.22 meq/g for control pore glass (CPG) and 0.25–0.50 meq/g for TG) is reported. To test the efficiency of these supports, we prepared nucleotide and oligonucleotide models, and their coupling yields and the purity of the crude detached materials were comparable to previously available results. These supports allow the facile and high-yield preparation of highly pure phosphodiester and phosphoramidate monoester nucleosides, conjugated oligonucleotides, and other yet unexplored classes of phosphodiester and phosphoramidate molecules.